2013
DOI: 10.7306/gq.1108
|View full text |Cite
|
Sign up to set email alerts
|

Mineral chemistry and thermobarometry of plutonic, metamorphic and anatectic rocks from the Tueyserkan area (Hamedan, Iran)

Abstract: 1 De part ment of Ge ol ogy, Bu-Ali Sina Uni ver sity, Hamedan, Iran Sepahi A. A., Borzoei K., Sa lami S. (2013) Min eral chem is try and thermobarometry of plutonic, meta mor phic and anatectic rocks from the Tueyserkan area (Hamedan, Iran). Geo log i cal Quar terly, 57 (3): 515-526, doi: 10.7306/gq.1108The study area is a part of the NW to SE strik ing Sanandaj-Sirjan meta mor phic belt in west ern Iran. The Alvand Pluton, consist ing of rocks that range in com po si tion from gab bro to gran ite, is the ma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(29 reference statements)
1
3
0
1
Order By: Relevance
“…For example, recently Azizi & Stern (2019) presented a propagating rift model to interpret Jurassic magmatism in the region, but on the basis of huge volumes of calc-alkaline plutonic rocks, this model may not be a model that correlates with geological observations. We agree with most other authors such as Torkian et al (2008), Shahbazi et al (2010), Agard et al (2011), Sepahi et al (2013, 2018) and Hassanzadeh & Wernicke (2016), who have argued for a subduction-related environment (continental arc or active continental margin) for a petrogenetic interpretation of the region in Jurassic time.…”
Section: Discussionsupporting
confidence: 93%
“…For example, recently Azizi & Stern (2019) presented a propagating rift model to interpret Jurassic magmatism in the region, but on the basis of huge volumes of calc-alkaline plutonic rocks, this model may not be a model that correlates with geological observations. We agree with most other authors such as Torkian et al (2008), Shahbazi et al (2010), Agard et al (2011), Sepahi et al (2013, 2018) and Hassanzadeh & Wernicke (2016), who have argued for a subduction-related environment (continental arc or active continental margin) for a petrogenetic interpretation of the region in Jurassic time.…”
Section: Discussionsupporting
confidence: 93%
“…Sepahi et al (2009) and Saki et al (2012) calculated peak metamorphic conditions of ~ 650-750 °C and ~ 2-4 kbar by means of conventional thermobarometry methods in migmatites occurring adjacent to the Alvand composite pluton. Maximum P-T conditions of 700-750 °C at 5-6 kbars were recently presented for the high-grade metamorphic mafic rocks from the metamorphic aureole around the pluton (Sepahi et al 2013). Based on amphibole composition and hornblende-plagioclase thermometry, thermobarometric calculations of Miri et al (2016) provided P-T conditions of 492-508 °C and 4.3-4.9 kbar for the cores of these minerals and 552-573 °C and 5.5-5.9 kbar for the outer rims, respectively.…”
Section: Fig 2 (Continued)mentioning
confidence: 99%
“…These geochronology studies suggest that CG gabbros emplaced at ≈161-167 Ma (Shahbazi et al 2010;Yang et al 2018). Furthermore, Sepahi et al (2013) used classic thermobarometry modelling to estimate emplacement temperatures of 1200-1300°C and 900-1100°C for Ol-gabbros and Hbl-gabbros, respectively, at crustal conditions of ≈ 5-6 ± 2.5 kbar for both.…”
Section: Geological Settingmentioning
confidence: 98%
“…The intrusive Alvand plutonic complex generated a welldeveloped thermo-metamorphic aureole made up of cordierite-andalusite-sillimanite-bearing hornfels and cordierite-bearing migmatites (e.g., Sepahi et al 2019;Saki et al 2020) in the local low-grade regional metamorphic basement (known in literature as "Hamedan Phyllite," e.g., Mohajjel et al 2003). Peak conditions for the thermal aureole were estimated at~750°C and 4 kbar (Sepahi 2008, Sepahi et al 2013Sepahi et al 2009Sepahi et al , 2013Sepahi et al , 2020Saki et al 2012Saki et al , 2020Baharifar et al 2004;Shahbazi et al 2014;Sheikhi Gheshlaghi et al 2020). The metapelitic migmatites show a U-Pb zircon age of~170 Ma (Sepahi et al 2019), and are mostly found in the eastern (Simin-Khaku locality) and southern (Tuyserkan locality) sectors of the inner aureole (e.g., Saki et al 2021).…”
Section: Geological Settingmentioning
confidence: 99%